THE IMPLEMENTATION OF THREE PHASE TECHNIQUE TO IMPROVE STUDENT’S READING COMPREHENSION AT THE TENTH GRADE OF LANGUAGE CLASS IN MAN MODEL 1 MANADO - Indah Wardaty Saud; Nur Halimah; Nikmala Nemin Kaharuddin; Lindawati Alimu (British : Jurnal Bahasa dan Sastra Inggris, 2021)
The aims of this study was to improve the achievement of student’s reading comprehension at the tenth grade of language class in MAN Model 1 Manado through the implementation of three phase technique. The subjects of this research were 24 students consisted of 13 males and 11 females. The data was collected by using test and observation of students and teacher’s activity. Then, the data was analyzed by using quantitative and qualitative instrument. The result obtained in the first cycle were, the average score of post-test was 74.17 with the percentage of Mastery as 50%, the percentage score of teacher’s activity in the first meeting was 12.8 % and in the second meeting was13.2%. While in the second cycle, the average score of post- test was 85 with the percentage of Mastery as 71%, the percentage score of teacher’s activity in the first meeting was 14.4% and in the second meeting was 15.6%. From the observation of students’ activity in the first cycle displayed that the students still could not ask the question related to the materials and convey a summary. On the other hand, in the second cycle based on the checklist, the students have accomplished all the indicators on the observation.Keywords: Three Phase Technique, Reading Comprehension